First onset of treatment of patients with eating disorders and treatment course: Results of data from a German health insurance company. (19th May 2022) - Herrmann, Kristin; Kaluscha, Rainer; Liebert, Alex; Spohrs, Jennifer; Gündel, Harald; von Wietersheim, Jörn
Abstract: Objective: This study examines, inpatient treatment costs, and typical treatment courses of patients with an eating disorder using secondary data. Method: The data were provided by a German health insurance company (data from 4.2 million members from 2004 to 2010; corresponds to a market share of 6% of all statutorily insured persons in Germany). An age and gender matched control group without an eating disorder diagnosis was assessed for comparisons from the same dataset. Results: Two thousand seven hundred and thirty four cases with an eating disorder diagnosis (anorexia nervosa [AN], bulimia nervosa [BN] or combination [ANBN]) were identified. The inpatient costs of treatment were €5471.15 for BN, €9080.26 for AN, €10, 809.16 for ANBN and €339.37 for the control group. Interestingly, there are numerous mild episodes of eating disorders that could be successfully treated solely on an outpatient basis with a short treatment duration. Conclusion: Our findings suggest that course and severity of eating disorders can vary from mild to very severe. Data from health insurance companies depict rather different disease and treatment courses than studies on primary data derived from treatment institutions. Key points: There are numerous patients with eating disorders with a mild episode, that could be successfully treated in only two quarters Patients with an eating disorder have conspicuously high treatments and treatment costs even before their initial diagnosis Patients who have a change in diagnosis appear to be sicker than patients who consistently have the same diagnosis